PENGARUH SPREAD, MARKET VALUE, VARIANCE RETURN DAN DIVIDEND PAYOUT RATIO TERHADAP HOLDING PERIOD SAHAM - Utami, Ni Luh Ayu Yulita; Sedana, Ida Bagus Panji (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2016)
The purpose of this study was to determine the effect spreads, market value, variance return and dividend payout ratio of the holding period of the stock chemical and basic industry sectors 2011-2014 period. The study was conducted using the method of non-participant observation, the data used is secondary data obtained in the Indonesia Stock Exchange (IDX) through the site www.idx.co.id. The sample used in the study of eight companies which were determined using purposive sampling method. The analysis technique used in this research is multiple linear regression. Based on the analysis, variable spreads had a negative influence is not significant, the market value has a significant negative effect, return variance has no significant negative effect and the dividend payout ratio has a significant positive pengeruh. Simultaneously independent variables significantly influence the holding period. Based on the results of this study should investors pay attention to the variable market value and the dividend payout ratio that has a significant influence on the holding period
Keywords: spread, market value, variance return, dividend payout ratio, holding period